Case report: Spontaneous rupture of leiomyosarcoma uteri 8 months after primary laparoscopic surgery of STUMP - Bicanin-Ilic, Marija; Ilic, Igor; Dimitrijevic, Aleksandra; Mujkovic, Srdjan; Jovic, Nikola; Rakic, Dejana; Arsenijevic, Neda; Nikolic-Turnic, Tamara; Balovic, Goran; Peric, Andjela; Mitrovic, Aleksandra; Nikolov, Aleksandar (Frontiers in Medicine, 2024)
Leiomyosarcoma, together with smooth muscle tumors of uncertain malignant potential (STUMP) and benign leiomyomas, belongs to a heterogeneous group of uterine neoplasms. According to the World Health Organization, tumors originating from uterus smooth muscle fibers are the second most frequent tumors. It is challenging to distinguish between STUMP and leiomyosarcoma because of an overlap of symptoms, lack of a precise definition, and unequivocal information obtained by imaging diagnostic methods. Following myomectomy or hysterectomy with laparoscopic or laparotomy surgery and a definitive histological diagnosis of STUMP, the course of treatment is determined by the need to preserve fertility. In 2014, the U.S. Food and Drug Administration published an alert that unprotected laparoscopic morcellation is correlated with a three-fold higher likelihood of dissemination of malignant cells and disease progression. Unprotected morcellation was independently associated with a higher risk of disease recurrence after demolition or conservative surgery, with a relative risk of 2.94. Hematoperitoneum resulting from the spontaneous rupture of a uterine tumor is a rare gynecological emergency, with very few cases reported in the last decade.